(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The article examines the integration of Information Technology (IT) in English for Specific Purposes (ESP) education for non-philological students. It highlights the use of Learning Management Systems (LMS) like Moodle and Blackboard to deliver specialized content, such as technical reading exercises and industry-specific vocabulary tests. The piece also discusses the role of virtual classrooms and online simulations in providing flexible, context-rich environments that enhance language skills, particularly in fields like medical English. Additionally, the article addresses how IT tools, including gamified learning platforms and collaborative applications, can boost student motivation and engagement. It emphasizes the need for careful implementation, adequate teacher training, and ensuring equitable access to technology to maximize the benefits of IT in ESP instruction. The conclusion underscores the potential of IT to create dynamic and personalized learning experiences, essential for students’ academic and professional success.